Self-reported mindfulness, cyclist anger and aggression. (September 2020) - Stephens, A.N.; O'Hern, S.; Young, K.L.; Chambers, R.; Hassed, C.; Koppel, S.
Highlights: The relationships between trait mindfulness, anger and aggression while cycling were examined. Cyclists with higher mindfulness reported less anger while cycling. Cyclists with higher mindfulness engaged in less aggression. Abstract: Anger is a common behaviour exhibited by road users when one's goals are perceived to have been blocked by another. Recent research has demonstrated that, generally, cyclists tend to deal with anger in constructive ways. However, when anger does manifest, it can result in behaviours that increase their crash risk. Amongst motor vehicle drivers, mindfulness levels have been associated with less anger and appear to mediate anger and associated aggression. The current study sought to understand whether mindfulness has similar associations with anger and aggression in a sample of cyclists. A total of 583 cyclists (males = 68 %) completed an online questionnaire that sought information on their levels of mindfulness, current mindfulness practices and tendencies for anger and aggression while cycling. The relationships between these were then examined using structural equation modelling. The results showed that cyclists with higher mindfulness levels tended to report less anger across a range of situations (e.g., interactions with pedestrians, cyclists, motor vehicle drivers and police). Both direct and indirect (through anger) relationships were found between mindfulness and aggression, again showing that more mindful cyclists tended to engage in less frequent aggression. These findings align with recent research investigating this relationship amongst motor vehicle drivers and suggest that mindfulness may be a promising strategy to reduce or avoid anger and aggression in cyclists.